URGENSI KODE ETIK PROFESI AKUNTAN DAN PERMASALAHANDALAM AUDIT LAPORAN KEUANGAN - Ade Vani Meilani; Aisah Ginting, AyonaArtia Sitohang, Aprillia Siahaan, Nasirwan (Jurnal Ekonomi dan Bisnis, 2025)
Accountants play a crucial role in the modern business world, where they act as providers of accurate, reliable, and relevant financial information, which is essential for various stakeholders to make informed decisions. The objective of this study is to explore the urgency of the professional accountant's code of ethics and the issues encountered in financial statement audits. The research employs a qualitative methodology with a literature review approach. The findings indicate that the code of ethics for public accountants is an essential component that ensures accountants perform their duties with high integrity and professionalism. This code serves as a moral guideline that not only establishes standards for professional conduct but also reflects the fundamental values underpinning the accounting profession. By emphasizing the importance of integrity, professionalism, and the avoidance of conflicts of interest, the code of ethics plays a role in maintaining the credibility of the accounting profession and protecting public interests. Violations of the code can damage the profession's reputation and diminish public trust in the financial statements presented. Financial statement audits face various issues that canimpact the reliability and quality of audit results. Human errors, fraud, changes in the business environment, and limitations in audit evidence are some of the main challenges that need to be addressed. Additionally, inherent risks, controls, and detection require special attention to ensure that audit outcomes are dependable. Effective management of audit risks and compliance with applicable auditing standards are key factors in ensuring the quality and consistency of audits.